Effects of NaCl and soy protein isolate on the physicochemical, water distribution, and mobility in frankfurters - Kang, Zhuang‐Li; Zou, Xiao‐Li; Meng, Lin; Li, Yan‐ping (International journal of food science & technology, 2021)
Summary In this study, we investigated the effect of gel and rheological properties, microstructure, and water distribution of frankfurters with various amounts of NaCl (1 and 2%) and soy protein isolate (SPI, 3 and 6%). The frankfurter cooking yield, a*value, and hardness significantly increased with the increasing NaCl and SPI content. However, the frankfurter springiness and cohesiveness were lower in the case of 6% SPI and 2% NaCl content than in the case of 3% SPI and 2% NaCl content. The thermal stability of myosin improved with the increasing NaCl and SPI, resulting in more compact and continuous structures. Meanwhile, the initial T2b, T21, and T22 relaxation times were significantly shorter, and the P21 and P22 peak ratios increased and decreased significantly, respectively, implying the increase of the immobile water content. Overall, the SPI use allowed the production of reduced‐salt frankfurter with desirable quality. Cooking yield and hardness were increased, and formed a compact and continuous structure with increasing NaCl and soy protein isolate which led to the immobile water was increased.